P1-S2.48 Exponential growth of Lymphogranuloma venereum diagnoses in the UK: Investigation of the largest documented outbreak among men who have sex with men. (10th July 2011) - Hughes, G; Alexander, S; Simms, I; Conti, S; Powers, C; Ison, C
Abstract : Background: With over 1500 cases reported, the UK now has the largest documented outbreak of Lymphogranuloma venereum (LGV) among men who have sex with men (MSM). Of particular concern is the recent exponential rise in cases—a third of all cases have been reported since 2010. We investigated the characteristics of this outbreak and specifically whether any factors were associated with the sharp upsurge in cases in 2010. Methods: The UK LGV Incident Group launched a diagnostic reference service and enhanced surveillance of LGV in the UK in October 2004. All symptomatic patients attending UK GUM clinics who were chlamydia-positive or contacts of positive cases were referred to STBRL in London and later also to the Scottish Bacterial Sexually Transmitted Infections Reference Laboratory in Edinburgh for confirmation. Enhanced LGV surveillance forms were completed by clinicians caring for cases and submitted to the HPA for analysis. An epidemic curve was plotted and the point of exponential growth estimated. The characteristics of cases prior to and during the exponential growth phase were compared. Results: Since 2003, 1570 LGV cases have been reported in the UK, of which 1268 (81%) had enhanced surveillance forms available. All but 8 (99%) were in MSM and most (77%) were seen in London, Brighton and Manchester. The point of exponential growth was estimated as 1st October 2009. Compared to cases prior to this date, cases in the growth phase were more likely to be older (41% vs 38% aged over 40), to be HIV positive (84% vs 78%), to be HCV antibody positive (27% vs 22%), to report unprotected anal intercourse (UAI) (80% vs 77%) and fisting (19% vs 14%), to present outside London (32% vs 27%), and to have acquired LGV in the UK (91% vs 87%). Overall, median case age was 38, 84% were white and 11% reported they acquired the infection outside the UK, mostly in Western European countries associated with the epidemic. UAI was reported by 78% of cases and at least 50 were identified as re-infections. Conclusions: LGV is becoming endemic in the UK and is characterised by HIV positive MSM involved in dense sexual networks. Although cases associated with the recent upsurge are more geographically widespread, there is no evidence of dispersal among lower risk or HIV negative MSM. LGV control will require intensified awareness raising and outreach among at risk populations. Regression modelling of key variables is underway to investigate and validate these findings.